Eksplorasi Ketergantungan Teknologi Dalam Novel “Dune” Karya Frank Herbert - Dimas Ikram Firmansyah; Reza Nafrendra Zain; Eva Dwi Kurniawan (Globe: Publikasi Ilmu Teknik, Teknologi Kebumian, Ilmu Perkapalan, 2024)
This journal analyzes the exploration of dependence on technology in the novel "Dune" by Frank Herbert. The main focus of the journal is on the technological concepts introduced in the story, including the use of Melange as an energy source for the Holtzman Drive, the development of artificial intelligence, shields versus laser weapons, as well as water distillation technology used by the Fremen. This journal explains the impact of dependence on technology in the political, social and economic context of the universe created by Herbert. This research also discusses the contradiction in the acceptance of technology between human needs and the prohibition on the use of computers in the history of the Dune universe.